The effectiveness of 0.5 mg and 1mg of semaglutide in patients with type two diabetes and predictors of response: a retrospective cohort study - Alenzi, Sara; Alzahrani, Abdullah; Aljaloud, Afnan; Alanazi, Kamayel; Alarfaj, Sumaiah J. (Frontiers in Endocrinology, 2024)
Background: Semaglutide is a glucagon-like peptide-1 receptor agonists (GLP-1-RAs) approved for the treatment of type 2 diabetes mellitus (T2DM) at doses up to 1 mg. The results from randomized control trials and real-world studies revealed that weekly semaglutide was associated with significant improvements in HbA1c and body weight. To our knowledge, no study assessed the effectiveness of using semaglutide for patients with T2DM in the Saudi population. We aim to assess the effectiveness of once weekly SC 0.5 and 1 mg of semaglutide on HbA1c and weight reduction in patients with T2DM in the Saudi population within 12 months of use, evaluate the predictors of response, and compare the effect of the two doses. Method: This is a retrospective cohort study conducted at Security Force Hospital in Riyadh, Saudi Arabia. Using electronic medical records of patients with type two diabetes who received semaglutide 0.5 or 1 mg for a total duration of at least 12 months of use. Results: Within the study period of semaglutide use, HbA1c significantly decreased from baseline by -2.1% (-2.3 to -1.91, 95% CI) (P <0.001). While the mean change in weight was -6.19 kg (-6.66 to -5.72, 95% CI) (P<0.001). Moreover, BMI, FBG, total cholesterol, LDL, and TG all decreased significantly from baseline (p<0.001). When comparing the sub-groups of 0.5 and 1 mg doses, although results were numerically favorable of 1 mg, there were no statistically significant differences in HbA1c % (-2.1 ± 1.8 vs. -2.1 ± 1.9, p-value= 0.934, respectively), and weight (-6.1 ± 5 vs. -6.2 ± 4.4 kg, p-value=0.837, respectively). Significant predictors of HbA1c reduction were the duration of DM, baseline HbA1c , and insulin therapy. While the significant predictor for weight reduction was insulin therapy. Conclusion: This study is document the effectiveness of once-weekly SC semaglutide on glycemic control and weight loss in real-world practice. We recommend a starting goal dose of 0.5 mg and gradual increase of dose based individual patient response. further studies are needed to assess the effectiveness and tolerability of various semagltude doses.